MANAGEMENT OF RHEUMATOID ARTHRITIS: SPECIAL CONSIDERATION FOR BIOLOGIC DISEASE-MODIFYING ANTIRHEUMATIC DRUGS - Abdul Razak, Salmi; Makmor-bakry, Mohd; Md Redzuan, Adyani (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Rheumatoid arthritis (RA) is a progressive chronic inflammatory disease affecting 0.5–1.0% of the adult population worldwide. Due to the damages caused by this autoimmune disease, new biologic therapies, particularly the biologic disease-modifying antirheumatic drugs (bDMARDs), are now being the treatment of choice in the management of RA. However, special precaution and prescreening before the usage of bDMARDs are needed to ensure better clinical response and avoiding risk of adverse event during treatment with the selected bDMARDs. In this review paper, we will provide overview on the incidence and pathogenesis of the disease, available pharmacological treatment and emphasizing special consideration in need on initiation of bDMARDs among RA patients. A literature review was performed by searching for relevant articles in Medline database through PubMed using medical subject headings terms and keywords: RA, bDMARDs, special consideration, tumor necrosis factor inhibitor, and non-tumor necrosis factor inhibitor. All papers reviewed were from 1999 to 2017 and were written in English. In this article, use of conventional synthetic DMARDs (csDMARDs), bDMARDs and special consideration to be taken upon initiation of biologic therapies in RA will be reviewed.